Elementary algebra 2e - Marecek, Lynn; Anthony-Smith, MaryAnne; Mathis, Andrea Honeycutt; OpenStax College; BC Open Textbook Project; BCcampus (OpenStax College, Rice University, 2020)
"Elementary Algebra - 2e is designed to meet scope and sequence requirements for a one-semester elementary algebra course. The book's organization makes it easy to adapt to a variety of course syllabi. The text expands on the fundamental concepts of algebra while addressing the needs of students with diverse backgrounds and learning styles. Each topic builds upon previously developed material to demonstrate the cohesiveness and structure of mathematics. The second edition contains detailed updates and accuracy revisions to address comments and suggestions from users. Dozens of faculty experts worked through the text, exercises and problems, graphics, and solutions to identify areas needing improvement. Though the authors made significant changes and enhancements, exercise and problem numbers remain nearly the same in order to ensure a smooth transition for faculty"--BC Campus website.
1. Foundations -- 2. Solving Linear Equations and Inequalities -- 3. Math Models -- 4. Graphs -- 5. Systems of Linear Equations -- 6. Polynomials -- 7. Factoring -- 8. Rational Expressions and Equations -- 9. Roots and Radicals -- 10. Quadratic Equations.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Includes bibliographical references and index.
Description based on online resource; title from pdf title page (viewed on June 23, 2020).
Keywords: Algebra -- Textbooks; Functions -- Textbooks; Electronic books